Fight books in comparative perspective. An introduction - Daniel Jaquet; Sixt Wetzler (Acta Periodica Duellatorum)
From the famous wrestling scenes of the Beni Hasan cemetery in Egypt to self-defence manuals of the globalised martial arts world of the twenty-first century: the depiction and description of body techniques of combat is a phenomenon that can be witnessed throughout history and across the world. For several hundred years, such techniques – pertaining to the use of edged weapons, impact weapons, and unarmed combat – have been laid down via image and/or text in a large number of fight books from various parts of the world. The volume “Fight Books in Comparative Perspective” collects the contributions to the conference of the same title that was held at Deutsches Klingenmuseum Solingen in 2017, and aims to open up an interdisciplinary discussion of the topic.